Fuzzy subbialgebras and duality - Chen, Wenjuan; Ge, Wenxu (Utilitas Mathematica, 2012)
In this paper, the fuzzy subbialgebras of bialgebras were studied systematically. At first, the definition of a fuzzy subbialgebra was introduced, and the related properties were investigated detailedly. Then the dual of a fuzzy subbialgebra was also discussed, and the results showed that the dual of fuzzy strong subbialgebras are fuzzy strong subbialgebras.